A Commentary on Towards autonomous artificial agents with an active self: Modeling sense of control in situated action - Hao, Chenxu; Russwinkel, Nele; Haeufle, Daniel F.B.; Beckerle, Philipp (Cognitive Systems Research, 2023)
Kahl et al., (2022) present a computational model of an autonomous agent implemented with an active self. With ideas based on the Free Energy Principle (Friston and Kiebel, 2009), their model tackles the challenge to unify higher-level cognitive activities and lower-level sensorimotor control as the autonomous agent maintains situational awareness while interacting with the environment. While Kahl et al., (2022) focus on modeling a single agent, we argue that this challenge similarly appears in modeling human–robot interaction (HRI). In this commentary, we discuss how the conceptual framework from Kahl et al., (2022) could inspire unified models of physical and cognitive HRI and how the modeling approach from Kahl et al., (2022) can potentially be applied to anticipatory thinking in robotics to support the human in daily life.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Anticipatory thinking; Human–robot interaction; Unified models of HRI